Effect of spraying nano iron and ascorbic acid on the physical and chemical characteristics of Mint plant (Mentha Pipreta L.) (Texas Journal of Agriculture and Biological Sciences, 2023)
This study was conducted in the agricultural research station- College of Agriculture and Marshlands, University of Thi Qar, Iraq. The paper presents the effect of spraying nano-iron and Ascorbic acid on some of the vegetative characteristics, chemical components and oil of the mint plant (Mentha pipreta L.), with three variants (0 control, 30 and 60) mg/l as nano-Iron source were tested, and three variants (0 control, 50 and 60) mg/l as Ascorbic acid source were tested. Results shown that the plants treated at a concentration of 60 mg/l with nano -iron fertilizer and Ascorbic acid were superior in plant height (28.11, 25.96) cm; leaves number (73.59,69.24)leaf/plant; branches number(16.90, 14.28)branch/plant; chlorophyll content in leaves (11.85, 10.77)mg/100 mg; total soluble carbohydrates (1.873, 1.563)mg/g; percentage of volatile oil in the leaves(0.6794, 0.6083 )%; amount of volatile oil per plant (0.286, 0.309)g. respectively.